Infrared thermometry to estimate crop water stress index and water use of irrigated maize in northeastern Colorado - Taghvaeian, Saleh, author; Chávez, José L., author; Hansen, Neil C., author; Molecular Diversity Preservation International, publisher (Colorado State University. Libraries, 2012)
With an increasing demand of fresh water resources in arid/semi-arid parts of the world, researchers and practitioners are relying more than ever on remote sensing techniques for monitoring and evaluating crop water status and for estimating crop water use or crop actual evapotranspiration (ETa). In this present study, infrared thermometry was used in conjunction with a few weather parameters to develop non-water-stressed and non-transpiring baselines for irrigated maize in a semi-arid region of Colorado in the western USA. A remote sensing-based Crop Water Stress Index (CWSI) was then estimated for four hourly periods each day during 5 August to 2 September 2011 (29 days). The estimated CWSI was smallest during the 10:00-11:00 a.m. and largest during the 12:00-13:00 p.m. hours. Plotting volumetric water content of the topsoil vs CWSI revealed that there is a high correlation between the two parameters during the analyzed period. CWSI values were also used to estimate maize actual transpiration (Ta). Ta estimates were more influenced by crop biomass rather than irrigation depths alone, mainly due to the fact that the effects of deficit irrigation were largely masked by the significant precipitation during the growing season. During the study period, applying an independent remotely sensed energy balance model showed that maize ETa was 159 mm, 30% larger than CWSI-Ta (122 mm) and 9% smaller than standard-condition maize ET (174 mm).
Keywords: crop water stress index; evapotranspiration; maize; northeastern Colorado